1986
DOI: 10.1099/0022-1317-67-11-2527
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Anti-peptide and Anti-poliovirus Type 3 Monoclonal Antibodies with Synthetic Peptides

Abstract: SUMMARYMonoclonal antibodies were prepared from mice immunized with an 18-residue synthetic peptide with an amino acid sequence from a major antigenic sequence involved in the neutralization of type 3 poliovirus. Approximately 250 hybridomas secreted antibodies that reacted with the peptide but not the virus, two antibodies reacted with the virus but not the peptide and no antibody reacted with both. Conversely 26 monoclonal antibodies prepared from mice immunized with type 3 poliovirus and known to be directe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…MAbs in the remaining two groups all recognized intact virus particles, judged by their capacity to precipitate them efficiently, but could be differentiated by their ability to neutralize (group 1) or not (group 2). The high proportion of MAbs found in this study that recognize both virus and peptide contrasts with a previous report by Ferguson et al (1986). This group raised approximately 250 MAbs to peptides representing an antigenic site on poliovirus type 3, but found that the vast majority were peptide-specific, and the two that bound to virus did not recognize immobilized peptide.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…MAbs in the remaining two groups all recognized intact virus particles, judged by their capacity to precipitate them efficiently, but could be differentiated by their ability to neutralize (group 1) or not (group 2). The high proportion of MAbs found in this study that recognize both virus and peptide contrasts with a previous report by Ferguson et al (1986). This group raised approximately 250 MAbs to peptides representing an antigenic site on poliovirus type 3, but found that the vast majority were peptide-specific, and the two that bound to virus did not recognize immobilized peptide.…”
Section: Discussioncontrasting
confidence: 54%
“…Crystallization studies of neutralizing anti-peptide MAbs with virus and peptides could provide valuable information on the requirements of peptide design necessary to achieve this objective, and such studies are underway with the group 1 MAbs. Anti-peptide MAbs may also prove useful in the evaluation of novel presentation systems for synthetic antigens, particularly during the manipulation of immunogenic sequences that are not recognized by anti-viral MAbs in isolation because these sequences normally contribute to conformational sites, as in the case of poliovirus peptides (Ferguson et al, 1986). In this context we have used the MAbs described here to compare the HRV2 sequence expressed at two locations on hepatitis B core antigen particles (Brown et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the sequences comprising 149-154 of VPI of a number of A subtype viruses (Weddell et al, 1985;Beck & Strohmaier, 1987) revealed that this region was reasonably conserved within a region of hypervariability, and often included only a single amino acid change. Based on this and also the observation that a single mutational change within an epitope may also enhance binding and neutralization by an antibody (Ferguson et al, 1986;Barnett et al, 1995) it was decided to determine if C 1.1 could cross-react with other A type strains. Preliminary assessment using a panel of 12-mer peptides encompassing VP1 residues 147-158 representing at least 17 different A strains indicated that almost all of the naturally occurring mutations within the minimum binding sequence abrogated binding.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced neutralization of a mutant virus (VP2 N163Y) was also seen with the anti-viral MAbs 801 and 829. Increased neutralization resulting from a single amino acid substitution has only been reported once previously (Ferguson et al, 1986). An anti-peptide M A b was shown to neutralize a mutant of poliovirus with a single substitution in VP1 threefold more efficiently than the parent virus.…”
mentioning
confidence: 90%